PROGRAM PENGENALAN DAN PENGUATAN EDUKODING PENDIDIKAN ANAK USIA DINI DI DESA SIDOMULYO PUNCU KEDIRI - Zahirotul Kamiliyah; Muhamad Safa'udin; Roizatul Faruk (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
Abstract: This community service program addresses the limited exposure of early childhood education (ECE) to digital literacy and computational thinking in rural areas. The focus of the program is to introduce basic coding concepts to children aged 3–7 years in Sidomulyo Village through an initiative called Edukoding. The aim is to foster logical thinking and digital readiness among young learners. Using a participatory action research approach, the program involved teachers, parents, and children in a series of training sessions, play-based coding activities, and digital parenting workshops. The results show increased teacher capacity in facilitating technology-integrated learning, active participation of children in coding games, and improved parental awareness of healthy digital use. The program also triggered social transformation through the formation of teacher learning groups and the emergence of local educational leaders. Edukoding demonstrates that coding can be introduced at an early age through context-based and inclusive strategies